Pengaruh Lingkungan Kelas Terhadap Hasil Belajar Bahasa Arab Siswa Kelas VIII MTsS Miftahussalam Karawaci - Salsabilunnisa; Sahlani; Faedurrohman (Penerbit Minhaj Pustaka, 2024)
Abstract The classroom environment is an external factor that plays an important role in supporting the achievement of student learning outcomes. A conducive environment includes the physical condition of the classroom, social relationships among students and between students and teachers, as well as a comfortable emotional atmosphere during the learning process. However, in reality, the Arabic learning outcomes of eighth-grade students at MTsS Miftahussalam Karawaci are still relatively low. This condition is suspected to be influenced by the suboptimal classroom environment. This study aims to determine the extent of the influence of the classroom environment on students’ Arabic learning outcomes. This research uses a quantitative approach. The sample consisted of 33 eighth-grade students of MTsS Miftahussalam Karawaci, which also served as the total population. Data collection techniques included questionnaires and documentation. The data were analyzed using simple linear regression. The results showed a correlation coefficient (R) value of 0.586, indicating a moderate positive relationship between the classroom environment and Arabic learning outcomes. The R Square value of 0.344 indicates that 34.4% of students’ Arabic learning outcomes are influenced by the classroom environment. Furthermore, the significance value of 0.000 (less than 0.05) indicates a significant influence of the classroom environment on students' Arabic learning outcomes. Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It can be concluded that the classroom environment has a significant influence on the Arabic learning outcomes of eighth-grade students at MTsS Miftahussalam Karawaci in the 2024/2025 academic year. Abstrak Lingkungan kelas merupakan faktor eksternal yang berperan penting dalam mendukung tercapainya hasil belajar siswa. Lingkungan yang kondusif mencakup kondisi fisik ruang kelas, hubungan sosial antar siswa maupun antara siswa dan guru, serta suasana emosional yang nyaman selama pembelajaran berlangsung. Namun, pada kenyataannya, hasil belajar Bahasa Arab siswa kelas VIII di MTsS Miftahussalam Karawaci masih tergolong rendah. Kondisi ini diduga dipengaruhi oleh kurang optimalnya lingkungan kelas. Penelitian ini bertujuan untuk mengetahui sejauh mana pengaruh lingkungan kelas terhadap hasil belajar Bahasa Arab siswa. Penelitian ini menggunakan pendekatan kuantitatif. Sampel dalam penelitian ini berjumlah 33 siswa kelas VIII MTsS Miftahussalam Karawaci, yang sekaligus menjadi total populasi. Teknik pengumpulan data dilakukan melalui angket dan dokumentasi. Data dianalisis menggunakan uji regresi linear sederhana. Hasil analisis menunjukkan nilai koefisien korelasi (R) sebesar 0,586 yang menunjukkan adanya hubungan positif sedang antara lingkungan kelas dan hasil belajar Bahasa Arab. Nilai R Square sebesar 0,344 menunjukkan bahwa 34,4% hasil belajar Bahasa Arab siswa dipengaruhi oleh lingkungan kelas. Selain itu, nilai signifikansi sebesar 0,000 (lebih kecil dari 0,05) menunjukkan bahwa terdapat pengaruh yang signifikan antara lingkungan kelas terhadap hasil belajar Bahasa Arab siswa. Dengan demikian, hipotesis alternatif (Ha) diterima dan hipotesis nol (Ho) ditolak. Dapat disimpulkan bahwa lingkungan kelas memiliki pengaruh yang signifikan terhadap hasil belajar Bahasa Arab siswa kelas VIII MTsS Miftahussalam Karawaci Tahun Ajaran 2024/2025.